Modeling a cost benefit transportation model to optimize the redistribution process: Evidence study from Sri Lanka - Jayarathna, D. G. N. D.; Lanel, G. H. J.; Juman, Z. A. M. S. (Journal of Sustainable Development of Transport and Logistics, 2021)
This study is a case study based on Softlogic Retail (Pvt) Ltd, Sri Lanka, which is a famous consumer electronics company and market leader in Sri Lanka. This company’s outbound logistics have been considered in this research, and they are mainly forced into the redistribution process in Sri Lanka. Extra routing costs due to unreasonable consumption of additional distance have been noticed in the current redistribution process. Here, this problem is modeled as a variant of the vehicle routing problem with a heterogeneous vehicle fleet. Our objective is to minimize warehouse operation, administration, and transportation costs by imposing constraints on capacity and volume. The researchers propose new heuristic solutions to the problem. A proposed heuristic algorithm has been used to find the optimal path between clusters. The computational investigation highlights the cost savings that can be accrued by this new heuristic. The cost savings can be accrued at a rate of as much as 37.5 % compared to the company’s existing method.
Keywords: vehicle routing problem, heterogeneous vehicle fleet, redistribution process, heuristic method.